Human Rights and Justice: Marine Waste Management for Environmental Protection and Ecosystem Sustainability in Indonesia - Cahyani, Ferina Ardhi; Jaya, Belardo Prasetya Mega; Wijaya, Dani (Universitas Negeri Gorontalo, 2023)
This article examines marine waste management in Indonesia, focusing on its impact on human rights, justice, and environmental sustainability. The accumulation of waste, particularly plastic, in Indonesia's vast maritime territory, has significant implications for human health, livelihoods, and the environment. As the country relies heavily on marine resources for food security and economic activity, pollution threatens the well-being of coastal communities, often exacerbating inequality and infringing on the right to a healthy environment. The research reveals that plastic waste is the most prevalent type found in Indonesian waters, highlighting the urgency of stronger regulatory enforcement. While Indonesia has regulations, such as Presidential Regulation No. 83 of 2018 concerning Marine Waste Management, their implementation remains insufficient. The study stresses the need for more robust policies addressing upstream and downstream waste management while ensuring accountability and equitable resource access. Effective enforcement requires collaboration between government agencies, private entities, and civil society, ensuring that vulnerable communities, especially those dependent on marine resources, are protected. Strengthening these efforts is crucial for the protection of marine ecosystems and advancing human rights and justice by safeguarding the right to a clean and healthy environment for all.